Understanding modifiable caregiver factors contributing to child development among young children in rural Malawi - Bliznashka, Lilia; Nwabuikwu, Odiche; Ahun, Marilyn; Becker, Karoline; Nnensa, Theresa; Roschnik, Natalie; Kachinjika, Monice; Mvula, Peter; Munthali, Alister; Ndolo, Victoria; Katundu, Mangani; Maleta, Kenneth; et al. (Wiley, 2024)
This study examined modifiable caregiver factors influencing child development in Malawi using baseline data from 1,021 mothers and their children <2 years of age participating in a cluster-randomized controlled trial implemented in rural Malawi (2022–2025). We fit an evidence-based theoretical model using structural equation modelling examining four caregiver factors: (1) diet diversity (sum of food groups consumed in the past 24 h), (2) empowerment (assessed using the project-level Women's Empowerment in Agriculture Index), (3) mental health (assessed using the Self-Reported Questionnaire, SRQ-20), and (4) stimulation (number of stimulation activities the mother engaged in the past 3 days). Child development was assessed using the Malawi Development Assessment Tool (norm-referenced aggregate Z-score). The model controlled for child, caregiver, and household socioeconomic characteristics. Results showed that caregiver dietary diversity was directly associated with higher child development scores (standardized coefficient 0.091 [95% CI 0.027, 0.153]) and lower SRQ-20 scores −0.058 (−0.111, −0.006). Empowerment was directly associated with higher child development scores (0.071 [0.007, 0.133]), higher stimulation score (0.074 [0.013, 0.140]), higher dietary diversity (0.085 [0.016, 0.145]), and lower SRQ-20 scores (−0.068 [−0.137, −0.002]). Further, higher empowerment was indirectly associated with improved child development through enhancement of caregiver dietary diversity, with an indirect effect of 0.008 (0.002, 0.018). These findings highlight the important role that caregiver diet and empowerment play in directly influencing child development and other aspects of caregiver well-being. Interventions aimed at enhancing child development should consider these factors as potential targets to improve outcomes for children and caregivers.